1980
DOI: 10.1111/j.1365-2133.1980.tb08138.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver changes in porphyria cutanea tarda patients treated with chloroquine

Abstract: In thirty-four patients with porphyria cutanea tarda treated with small doses of chloroquine, liver biopsies were performed before and after treatment. In seventeen cases (50%) the morphological patterns before treatment corresponded to unstabilized fibrosis, while in eleven (32.4%) there were non-specific changes in the form of focal fatty change, haemosiderosis, and mild fibrosis of the portal tracts. Active chronic hepatitis was found in three patients (8.8%), and cirrhosis also in three cases. Although in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 6 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…Chloroquine administration is followed by increased urine excretion of pophyrins 125 and slight increase in hepatic transaminases at the beginning of treatment. 124 Chloroquine does not worsen hepatic injury 124,126 nor causes retinopathy, when used in low doses. 127 Bullae and cutaneous fragility improve in approximately 6 months and the porphyrin excretion normalizes between six to 15 months.…”
Section: Treatmentmentioning
confidence: 99%
“…Chloroquine administration is followed by increased urine excretion of pophyrins 125 and slight increase in hepatic transaminases at the beginning of treatment. 124 Chloroquine does not worsen hepatic injury 124,126 nor causes retinopathy, when used in low doses. 127 Bullae and cutaneous fragility improve in approximately 6 months and the porphyrin excretion normalizes between six to 15 months.…”
Section: Treatmentmentioning
confidence: 99%
“…Based on the findings thus far, we speculated that blocking the autophagic degradation of COX6A1 may be a promising intervention against gefitinib-induced hepatotoxicity. It might be rational to consider CQ or another popular autophagy inhibitor hydroxychloroquine as an intervention agent, but since both have been reported to cause liver abnormalities [ 29 , 30 ]. In addition, the results showed in Figure S5D suggested that CQ could accumulate the portion of COX6A1 in the cytoplasmic fraction while could not rescue the level of COX6A1 in the mitochondrial fraction under gefitinib treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The delay in therapeutic effect can be tentatively related to the indirect action of venesection which probably depends on the removal of iron, one putative factor in the development of PCT (Kushner, 1982). On the other hand, the prompt beneficial effect of hydroxychloroquine may simply be attributed to its specific ability to mobilize and remove lysosomal stores of porphyrins (Chlumska et al, 1980;Malkinson & Levitt, t98o;Riches, Morris & Stanworth, 1981;Harder, Pakaiapati & Debuch, 1981). However, more complex biological interactions of the drug with cellular structures such as mitochondria, which are a site of porphyrin biosynthesis (Kowertz, 1976), cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…^- Cainelli et al 1970;Walsh et al, 1970;Grossman et al, t979;Di Padova et al, 1983) or hydroxychloroquine (Vogler, Galambos & Olanski, 1970;Chlumska, Chlumsky & Malina, 1980;Malkinson & Levitt, 1980) have salutary effects on the clinical and biochemical hallmarks of PCT.…”
mentioning
confidence: 99%